Stereoselective Synthesis of N-Glycosyl Oxazolines and Evaluation of Their Antiproliferative Activity - Grigorii G. Sivets; Aleksey V. Sivets; Maksim A. Khancheuski (Journal of New Developments in Chemistry, 2023)
A stereoselective synthesis of protected N-glycosyl oxazolines has been developed from available acylated sugar 1,2-O-acetonides using intramolecular Ritter-like reactions. New N-α- and β-D-pentofuranosyl, α-D-hexofuranosyl oxazolines as valuable intermediates for preparation of diverse N-glycosides were obtained by BF3.OEt2-KHF2 or BF3.OEt2-promoted reactions of pentofuranose and hexafuranose acetonide derivatives with nitriles. When selectively acylated D-xylo- or ribofuranoses were employed in the reactions, N-α-pentofuranosyl oxazolines were prepared in good yields. A mechanism for the formation of glycosyl oxazolines was proposed. A series of oxazoline derivatives were evaluated for their antiproliferative activity on three human cancer cell lines (MCF-7, Hela and K562).
Keywords: ketal and acyl-protected carbohydrate derivatives